Persepsi Harta Bersama Menurut Hukum Islam dan Hukum Positif Indonesia: The Perception of Joint Property According to Islamic Law and Positive Law in Indonesia - Anri, Andi Fini Rathi (ISTIDLAL, 2023)
This article focuses on the issue of joint property or marital property that arises as a result of marriage between men and women in Indonesia. The matter of marital property is interesting to examine, considering that the issue of joint property arises as a consequence of divorce, which is a possibility in a marriage. In fact, culturally, discussing joint property is still considered taboo in Indonesian society in general. People tend to trivialize this issue because of cultural perceptions that consider marriage as sacred, holy, noble, and eternal, making it inappropriate to discuss before the marriage takes place. However, addressing joint property before marriage can provide certainty regarding the assets involved before the marriage is consummated. This research employs a normative research type with a statutory approach and a conceptual approach. At the very least, this study offers an in-depth analysis of joint property arising in a marriage, viewed from the perspectives of Islamic law and positive law in Indonesia.